Os recenseamentos eleitorais como fonte para o estudo das elites no decurso da Monarquia Constitucional : da Regeneração à República - Cruz, Maria Antonieta (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
This paper aims to highlight the pivotal role of Electoral Lists in research on Political and Social History. It studies the legislative support originating those lists within the chosen period, and also the conditions of the making of that support, the diversity within it and the frailties and merits of the documents as a whole. Using as case studies the results of prior multiple research based on Electoral Lists Records, I intend to demonstrate their potential as a source in the study of the Elites.